Catalytic wet torrefaction of lignocellulosic biomass: An overview with emphasis on fuel application - Frederick Jit Fook Phang; Megan Soh; Deni Shidqi Khaerudini; Gerald Ensang Timuda; Jiuan Jing Chew; Bing Shen How; Soh Kheang Loh; Suzana Yusup; Jaka Sunarso (South African Journal of Chemical Engineering, 2023)
Wet torrefaction (WT), also named hydrothermal carbonisation (HTC), has been regarded as one of the highly studied thermochemical process pathways for biomass-to-solid fuel conversion in the last decade (2012–2021). Catalysts have been added in the WT or HTC of lignocellulosic biomass for various applications (i.e. solid fuel synthesis, carbon material synthesis, pre-treatment, sugar production, ash content removal, and the study of reaction kinetics). Regardless, there is no review on the addition of catalysts in WT to produce hydrochar as fuel, specifically on the role of catalysts in the formation of ‘secondary deposits’, which refers to deposits that have been observed on the hydrochar. This review discusses the fundamentals of WT and how the lignocellulosic biomass components in various biomass, operating process parameters, and catalysts affect the fuel properties of the hydrochar product. For catalytic WT and HTC, relevant studies in different yet interrelated applications are overviewed, where insights are given based on the effect of catalyst addition on the properties of hydrochar and the promotion of ‘secondary deposits’. The ‘secondary deposits’ established in carbon material synthesis studies can reveal the relationship between catalyst addition and formation. On top of that, it also serves as a complimentary knowledge to enhance the understanding of how these deposits can be used to increase the higher heating value of the hydrochar, which is lacking in the existing hydrochar synthesis studies. Therefore, the aim of this review is to provide insights into the addition of catalysts for the synthesis of hydrochar for fuel application.